"What matters to me": A multi‐method qualitative study exploring service users', carers' and clinicians' needs and experiences of therapeutic engagement on acute mental health wards. (18th January 2021) - McAllister, Sarah; Simpson, Alan; Tsianakas, Vicki; Robert, Glenn
Abstract: Nurse–patient therapeutic engagement on acute mental health wards is beneficial to service users' outcomes and nurses' job satisfaction. However, engagement is not always fulfilled in practice and interventions to improve engagement are sparse and ineffective. We explored the experiences of service users, carers, and clinicians drawing from 80 hours of non‐participant observations in an acute mental health ward and semi‐structured interviews with 14 service users, two carers, and 12 clinicians. Analysis of these data resulted in 28 touchpoints (emotionally significant moments) and eight overarching themes. Service users, carers, and clinicians identified a lack of high‐quality, person‐centred, collaborative engagement and recognized and supported efforts to improve engagement in practice. Potential solutions to inform future intervention development were identified. Our findings align with previous research highlighting negative experiences and support the need to develop multicomponent interventions through participatory methods.